The act and art of editing: exploration of the functions and responsibilities of book editors in the electronic age (2023)
In this present ICT-driven information age, the traditional roles of editors in the book publishing process are threatened, as software is being developed to perform editorial functions. Experience has shown, however, that ICT can help in improving human experience in all spheres of life. For editors to remain relevant, there is the need for conscious effort by publishers and editors to upgrade their knowledge in the application of ICT in the editorial practices. This paper examines the chances of survival of book editors in the face of a fast changing environment. The paper concludes that the publishing option in the electronic age does not exclude editorial functions but redefines the new roles of editors in the publishing process. Therefore, editorial roles need a redefinition in the present dispensation and editors and publishers, especially in the developing nations such as Nigeria need to move with the changing time. This is done by committing more resources into training and development, to enable editorial staff to be relevant in the present dispensation. Therefore, the job of the editor remains, only if, editors upgrade themselves in the act and art of editing to make them relevant in this changing time.